Ectopic Breast Tissue of the Vulva in a Postmenopausal Woman - Sasha Mikhael; Wesley Nilsson; Kruti Patel; Sherri Graf (Hindawi Limited, 2017)
Ectopic breast tissue is a rare condition caused by remnants of the mammary ridges that fail to involute during embryologic development. To date, only 39 cases have been reported in the literature worldwide. Here, we report the 40th case of a 69-year-old G3P2 postmenopausal Caucasian woman who presented with complaint of vulvar swelling. Biopsy of the mass revealed the presence of a benign mammary gland-like adenoma which was completely excised shortly thereafter. Clinical presentation of vulvar breast tissue is highly variable depending on the amount of breast tissue developed and its functionality. Diagnosis is ultimately made by tissue biopsy and histopathologic examination. Due to the scarce evidence that exists pertaining to supernumerary breast tissue located on the vulva, specific management guidelines are lacking. Since this ectopic tissue serves no function, but rather may provide a source for future malignancy, surgical excision is recommended.